ONE CRISIS WITHIN ANOTHER: COPING WITH DOMESTIC VIOLENCE DURING THE COVID-19 PANDEMIC - Noorfara Atilia Karim; Sajaratulnısah Othman; Rosmawanı Che Hashim; Norbani Che Ha (International Journal of Health Services Research and Policy)
Although Covid-19 has aggravated and initiated mental health concerns to domestic violence (DV) victims, there is a worrying lack of measures meant to DV victims in the context of a pandemic. This study aims to (a) identify and understand the types of domestic violence experienced by women during the pandemic, as well as the consequences in social and work contexts, (b) assess the coping strategies of abuse victims, and (c) identify the gap in government and organizational support for DV victims. A semi-structured questionnaire was used to conduct in-depth interviews with 19 Malaysian women. NVIVO 8 was utilised for thematic analysis. The qualitative findings suggest that there was an increase in gender-based violence in Malaysia during the lockdown, with psychological abuse appearing to be the most prevalent. Despite the difficulties, the majority of victims who were exploited during the lockdown did not report the abuse and instead employed avoidance-based coping mechanisms. Negative passive-avoidance and negative active-avoidance were the most prevalent coping mechanisms. The findings also indicate that eradicating domestic violence would necessitate a broader, more coordinated, and integrated system of government and organizational support. This is the first study to evaluate the serious impact of domestic violence on working Malaysian women in the wake of the Covid-19 crisis. As a result, it provides a wealth of information and could serve as a firm basis for designing effective psychological interventions for women in countries with similar cultural and societal norms to Malaysia.